Crystal Structure Analysis of 2,3,4-Tri-O-acetyl-a-methyl-D-glucopyranoside - Zhen, Xiao-Li; Zhou, Zhen; Han, Jian-Rong; Tian, Xia; Liu, Shouxin (Asian Journal of Chemistry, 2015)
2,3,4-Tri-O-acetyl-a-methyl-D-glucopyranoside (F.W. 319.28) was synthesized, characterized by 1H NMR, confirmed by X-ray crystal structure analysis. This compound crystallizes in monoclinic class under the space group orthorhombic P2(1)2(1)2(1) with cell parameters a = 9.0312(18) Å, b = 11.731(2) Å, c = 15.139(3) Å; Z = 4. The structure exhibits inter-molecular hydrogen bonds of the type O-H---O, C-H---O.